Temperature and concentration dependences of specific heat of Bi₁₋ₓSbₓ solid solutions - Rogacheva, E. I.; Doroshenko, A. N.; Nashchekina, O. N. (Науково-технологічний комплекс "Інститут монокристалів", 2018)
For Bi₁₋ₓSbₓ solid solutions, the concentration (x = 0 - 0.12) and temperature (170-525 K) dependences of specific heat Cp were obtained. At all temperatures studied, three peaks of Cp were observed near x = 0.015, x = 0.037, and x = 0.07. The observed effects were attributed to critical phenomena accompanying the second-order phase transitions: percolation transition from dilute to concentrated solid solutions, the transition to a gapless state, and the semimetal-semiconductor transition, respectively. It was shown that the values of critical indexes (α = 0.11 ± 0.01) are the same not only for different peaks but also for different temperatures and correspond to the values theoretically calculated within the framework of scale-invariant theory for three-dimensional (3D) models.

Для твердих розчинів Bi₁₋ₓSbₓ одержано концентраційні (x = 0 - 0.12) та температурні (170-525 K) залежності питомої теплоємності Cp. При всіх температурах, що досліджувалися поблизу x = 0.015, x = 0.037 та x = 0.07 спостерігаються піки Cp. Це пов'язується із критичними явищами, які супроводжують переходи другого роду: перколяційний перехід від розведених до концентрованих твердих розчинників, перехід у безщілинний стан і перехід напівметал-напівпровідник відповідно. Показано, що значення критичних індексів (α = 0.11 ± 0.01) однакові не тільки для різних піків, але також для різних температур і відповідають значенням, які теоретично розраховані у межах масштабно-інваріантної теорії для тривимірної (3D) моделі.
Температурні та концентраційні залежності питомої теплоємності Bi₁₋ₓSbₓ твердих розчинів
Keywords: solid solutions; composition; temperature; specific heat; phase transition